Pengaruh Kecerdasan Emosional Terhadap Etika Komunikasi Remaja Karang Taruna Lingkungan RT 005 Mustika Jaya Bekasi - Alisya Fairuz Zahira; Adinda Salsabila; Cindy Febbiola; Dhisva Putri; Fildza Aulia Rahma; Haya Thabitah Nayanthi; Heri Sandi; Hilda Agny Muanih; Kamayla Imara; Meilvia Maulidina; Monica Theresa; Noneng Fidela; Syifa Nur Fiqhiyah; Yoni Afiliansyah; Murtiadi, Murtiadi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to analyze the influence of emotional intelligence on the communication ethics of Karang Taruna teenagers in the RT 005 Mustika Jaya Bekasi environment, with the background that emotional intelligence is a key factor in forming effective and ethical communication among teenagers. Emotional intelligence, which includes the ability to recognize, understand, and manage one's own and others' emotions, is believed to play an important role in encouraging ethical communication behavior, such as honesty, responsibility, and respect for others. Karang Taruna teenagers as an age group that is experiencing dynamic emotional and social development, often face challenges in maintaining communication ethics due to low emotional intelligence, which can trigger internal conflicts, misunderstandings, and decrease the quality of social interactions. Through a quantitative approach, this study examines the relationship between emotional intelligence and communication ethics, with the hope of providing both practical and academic contributions in efforts to strengthen the character of the younger generation who are able to communicate politely, ethically, and build positive social relations in society, especially in youth organizations such as Karang Taruna RT 005 Mustika Jaya Bekasi.